La fabrique des plantes globales. Une géographie de la mondialisation des végétaux d’Amazonie - Bastien Beaufort (Confins)
Far from being an under-populated, wild or pristine region, the Amazon rainforest appears on the contrary to be a maker of global plants. What are the mechanisms of the globalization of Amazonian plants? We will see through this article that the globalization of Amazonian plants is based on a set of socio-ecological processes through time and space that we call layers of mondialisation which, when combined, shape the globalization of crops. These layers are structured around global commodity chains that are fed by an extractivist-capitalist logic. The comprehension of the making of global plants appears to be a necessary condition for implementing a fair repartition of the richness issued from biodiversity, from which Amazonian people and the region did not really benefit.